Urachal mixed adenocarcinoma and small cell neuroendocrine carcinoma with widespread metastasis and resistance to chemotherapy: a case report - Sarah Obiedat; Khaled Murshed; Lajos Szabados; Khaled Al Rumaihi; Issam Al Bozom (BMC, 2024)
Abstract Neuroendocrine carcinoma arising from the urachus is extremely rare. We describe a case of a 33-year-old gentleman who presented with hematuria and diagnosed to have a composite adenocarcinoma and small cell neuroendocrine carcinoma arising from the urachus. The patient also had widespread metastasis at the time of presentation, therefore, he was referred for chemotherapy. However, the disease showed progression despite treatment. Recognition of neuroendocrine carcinoma component in urachal tumors, although rare, is very essential as this histologic type carries poor prognosis with aggressive clinical outcome.